Comprehensive analysis on the regulatory mechanism of active ingredient accumulation during fermentation process of Massa Medicata Fermentata: microbe and metabolic profiles - Li, Yun; Wang, Ya-Juan; Guo, Xiao-Peng; Zhao, Hong-Yuan; Ren, Hai-Wei; Li, Hong-Yu (Frontiers in Microbiology, 2025)
BackgroundMassa Medicata Fermentata (MMF) is a traditional medicinal/edible fermented product; however, comprehensive research on the fermentation process from a microscopic perspective remains limited. In this study, we aimed to investigate the dynamic changes and correlations of physicochemical properties, microbial communities, and metabolite profiles in different fermentation stages (0, 48, 72, and 96 h) of MMF.MethodsStandard analytical tests, microbiome sequencing, broad-target metabolism, mixed standard-based mass spectrometry, and fine structure analysis were integrated to elucidate fluctuations in physicochemical, microbial, and metabolic levels during MMF fermentation.ResultsDuring the fermentation process, bacterial diversity generally shows an increasing trend, whereas fungal diversity generally shows a decreasing trend. Revealing that the differentially abundant metabolites were primarily categorized into lipids, amino acids and derivatives, phenolic acids, organic acids, flavonoids, lignans and coumarins, nucleotides and derivatives, and alkaloids. Structural equation modeling and correlation analysis indicated that two species of bacteria (Bacillus velezensis, Bacillus safensis) and four species of fungi (Apiotrichum montevideense, Geotrichum bryndzae, f_Dipodascaceae, Saccharomycopsis fibuligera) showed significant positive correlations with five types of differential metabolites, including lipids, flavonoids, phenolic acids, lignans and coumarins, and organic acids. These differential metabolites are essential components responsible for the therapeutic effects of MMF, particularly those that reach peak concentrations at 72 h of fermentation.ConclusionThese findings are expected to provide a reference for developing strategies to strengthen the quality of MMF and promote its modern application.